2022
DOI: 10.3389/fcimb.2022.1009901
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs associated with the pathogenesis and their role in regulating various signaling pathways during Mycobacterium tuberculosis infection

Abstract: Despite more than a decade of active study, tuberculosis (TB) remains a serious health concern across the world, and it is still the biggest cause of mortality in the human population. Pathogenic bacteria recognize host-induced responses and adapt to those hostile circumstances. This high level of adaptability necessitates a strong regulation of bacterial metabolic characteristics. Furthermore, the immune reponse of the host virulence factors such as host invasion, colonization, and survival must be properly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 178 publications
0
1
0
2
Order By: Relevance
“…El miRNA 146b ha sido asociado a la regulación de diversas vías de señalización y algunos de sus genes blanco descritos son AKT3, IL6, IRAK1, NFKB1, TLR4 (15) ; y se ha reportado que se sobre expresa en el suero de pacientes con TB activa (16) . El miR-155 modula la producción de mediadores inflamatorios en respuesta a estímulos microbianos regulando negativamente la expresión de TAK1 y la proteína de unión a TRAF6.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…El miRNA 146b ha sido asociado a la regulación de diversas vías de señalización y algunos de sus genes blanco descritos son AKT3, IL6, IRAK1, NFKB1, TLR4 (15) ; y se ha reportado que se sobre expresa en el suero de pacientes con TB activa (16) . El miR-155 modula la producción de mediadores inflamatorios en respuesta a estímulos microbianos regulando negativamente la expresión de TAK1 y la proteína de unión a TRAF6.…”
Section: Introductionunclassified
“…El miR-155 modula la producción de mediadores inflamatorios en respuesta a estímulos microbianos regulando negativamente la expresión de TAK1 y la proteína de unión a TRAF6. También se ha observado que, en la infección por TB, miR-155 se sobre expresa e inhibe la autofagia inducida por IFN-γ; algunos de los genes blanco a los que ha sido asociado son AKT1, APAF1, ATP6V1H, CASP3 (15) . Interesantemente, miR-155 tiene doble función durante la infección con TB; por un lado, mantiene la supervivencia de los macrófagos infectados con Mtb y, por otro lado, promueve la supervivencia y la función de las células T específicas de Mtb (17) .…”
Section: Introductionunclassified
“…The increased expression of circAGFG1 in alveolar lavage fluid of ATB patients can inhibit the apoptosis of M. tb-infected macrophages and promote autophagy through the circAGFG1/miR-1257/Notch2 axis ( Shi et al, 2020 ). NcRNAs also have the potential to serve as diagnostic markers, therapeutic targets or therapeutic evaluation indicators for TB ( Davuluri and Chauhan, 2022 ; Hemati et al, 2022 ; Liang et al, 2022 ; Wang L. et al, 2022 ; Wang Q. et al, 2022 ; Zhang et al, 2022 ). Studies found that the upregulated hsa_circ_0001953, hsa_circ_0009024, hsa_circ_051239, hsa_circ_029965 and hsa_circ_404022 and the downregulated hsa_circ_0001380 and hsa_circRNA_103571 in the serum and the downregulated NONHSAT101518.2, NONHSAT067134.2, NONHSAT148822.1, and NONHSAT078957.2 in serum exosomes could be used as potential biomarkers for patients with ATB disease ( Huang et al, 2018 ; Yi et al, 2018 ; Luo et al, 2020 ; Fang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each specific miRNA can have hundreds of different targets that affect entire gene expression networks [3]. miRNAs have been implicated in many diseases, and regulate the immune response of hosts infected with bacteria such as Treponema pallidum [4], Helicobacter pylori [5], Mycobacterium avium [6], M. tuberculosis [7], Salmonella [8], and Listeria monocytogenes [9]. Hence, understanding the expression pattern of miRNAs could potentially lead to the development of novel diagnostic biomarkers for various complicated microbial infectiondriven inflammatory diseases, including periodontal disease (PD).…”
Section: Introductionmentioning
confidence: 99%